Case studies: Dry eye in a pandemic. Issue 10 (October 2020) - Harvey, Bill
Abstract : Bill Harvey introduces the first in a series of case studies from readers reflecting the sorts of patient presentations that are increasingly being dealt with by eye care professionals since the start of the Covid-19 pandemic. This week we look at two cases sent in by contact lens optician Beth Ralph